Doctor of Physical and Mathematical Sciences, Professor M.T.Genaliev is 70 years old - Ramazanov, M.I. (Bulletin of the Karaganda University. Mathematics Series, 2017)
On January 25, 2017, a well-known specialist in the field of the theory of partial differential equations and its applications, chief researcher at the Institute of Mathematics and Mathematical Modeling of the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan, Doctor of Physical and Mathematical Sciences, Professor Muvasharkhan Tanabaevich Jenaliyev turned 70 years old.